Ketersediaan Debit Air untuk Irigasi Pedesaan di Sungai Cipeles Jawa Barat - Supadi, Supadi (MEDIA KOMUNIKASI TEKNIK SIPIL, 2007)
Indonesian’s gorvernment has make regulation No.7, 2004, about water resources engineering. It also content in Principle Ordinance of Indonesia 1945 in chapter XIV, and in section 33 which says that the land, the water and the rich of Indonesian’s nature is having by the government and used to as much as the civilian prosperity.Some initiatives has made by the government to increase the number of food production. They are consist of two ways, intensification and extensification methods which are suported by technical, semi technical, and simple technical irrigation system. Because of the Growth of Indonesian’s population, the demand of rice as main food is increase.Water demand research for village irrigation is needed to increase the production of rice. To estimate the demand of water, it is a must to have investigation first. The investigation is used to investigate some datas, they are the dimension of river chanall, the speed of water and the discharge of river. There are two method to looking for them. First method is using the floating object and then the second one is using Current Meter. Using Floating Object is suitable to looking for the datas in a village irrigation system, but it is a must to use another equipment as equal equipment. Keywords : Water Demand, Village  Irrigation